История Харьковского университета при действии устава 1884 г. (с 1884 до 1905 г.) - Бузескул, В.П.; Buzeskul, V.P. (Харьков: Типография Адольфа Дарре Kharkov: Adolf Darre's Printing House, 1905)
Владислав Петрович Бузескул (1858–1931) —историк-античник, историограф, академик АН СССР (1922), академик НАНУ (1925). Занимал должности приват-доцента и профессора Харьковского университета (1885—1924). Научно-литературная деятельность Бузескула весьма разнообразна, но главные труды его относятся к области древнегреческой истории. Несколько его работ посвящены истории Харьковского университета. Buzeskul Vladislav Petrovich (1858-1931), historian, historian, academician of the Academy of Sciences of the USSR (1922), Academician of the National Academy of Sciences (1925). He held the positions of assistant professor and professor of Kharkov University (1885-1924). Buzeskul ’s Scientific and literary activities are very diverse, but his main works are in the area of ancient Greek history. Several of his works are devoted to the history of the Kharkov University.
History of Kharkov University in the statute in 1884 (from 1884 to 1905)
Keywords: Харьковский университет; устав 1884 г.; строй университета; попечитель округа; гонорар; семестр; ректор; доцент; история Харьковского университета; Kharkov University; the history of Kharkov University; the charter of the University in 1884; the Council of the University; formation of the University; Rector; District Trustee